2015
DOI: 10.1890/es14-00342.1
|View full text |Cite
|
Sign up to set email alerts
|

Environmental drivers of deadwood dynamics in woodlands and forests

Abstract: Abstract. Deadwood dynamics play a key role in many forest ecosystems. Understanding the mechanisms involved in the accumulation and depletion of deadwood can enhance our understanding of fundamental processes such as carbon sequestration and disturbance regimes, allowing better predictions of future changes related to alternative management and climate scenarios. A conceptual framework for deadwood dynamics has been generally accepted but has not been broadly tested with empirical data. We used a large (n ¼ 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 53 publications
1
21
0
1
Order By: Relevance
“…Higher amounts of CWD, as snags, logs and stumps, were related to biomass [45,64,82,91]. It is worth noting that in the study area, the stand volume in the EAC was the highest, consequently differences between the accessibility classes are again associated with differences in the accumulation of CWD.…”
Section: Rss Rdt Rst Rdw and Rdsmentioning
confidence: 77%
See 1 more Smart Citation
“…Higher amounts of CWD, as snags, logs and stumps, were related to biomass [45,64,82,91]. It is worth noting that in the study area, the stand volume in the EAC was the highest, consequently differences between the accessibility classes are again associated with differences in the accumulation of CWD.…”
Section: Rss Rdt Rst Rdw and Rdsmentioning
confidence: 77%
“…Forest management intensity affects the deadwood volume, which decreases from extensive management to intensive management [44]. Several studies showed that the volume of CWD in natural forest stands is proportional to the biomass of living trees at the site [45][46][47], although an amount of CWD varying greatly was found. In reserves characterized by beech forests in Europe, Christensen et al [48] indicated an average volume of 130 m 3 ha −1 , a value varying greatly which can exceed 700 m 3 ha −1 in reserves with a long history of protection.…”
Section: Human Accessibility Classes and Cwd Amountmentioning
confidence: 99%
“…This increase was driven by both above‐ and belowground carbon pools. As forests develop toward late‐seral stages, mortality of canopy trees increases through both density‐dependent and density‐independent processes (Franklin et al, ), leading to dead tree recruitment and deadwood accumulation (Garbarino, Marzano, Shaw, & Long, ) (Figure a). However, our data suggest that the increase in deadwood occurs concurrently with increases in ALC (Figure a), which is a much larger carbon pool than deadwood in our study system (e.g., up to an order of magnitude larger in 200 year old forests).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, relatively continuous senescence or persistent pathogens can cause partial or selective mortality of older trees, leading to large dead wood accumulation in aging aspen stands (Brown and Simmerman , Garbarino et al. ). Moreover, as large trees die and create canopy gaps, stands may develop multi‐cohort size structures (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…If aspen communities are largely fire independent and stable, we expected to find negative exponential relationships between tree size (or age) and density at both stand and landscape scales, indicating both localized capacity for self-replacement and regional stability (e.g., Rubin et al 2006). Continuous or episodic mortality of large trees (e.g., from pathogens, drought) would be expected in stable stands, facilitating regeneration via canopy openings and contributing to structural complexity (e.g., Garbarino et al 2015). In contrast, if aspen communities are primarily fire-dependent and seral, most stands would be expected to contain relatively few cohorts, and size-and age-class distributions at landscape scales would have a negative exponential form only if fire or other stand-replacing disturbance was frequent enough to maintain a majority of the landscape in young stands (Van Wagner 1978), an unlikely scenario if past fire exclusion led to a fire deficit.…”
Section: Introductionmentioning
confidence: 99%